Renal cortex echogenicity increases degree of retinopathy in diabetes mellitus - Indah Maulidawati; Abdurrahim Rasyid Lubis; Dharma Lindarto (Universa Medicina, 2016)
BackgroundThe number of people with diabetes mellitus (DM) is increasing due to population growth, aging, and increasing prevalence of obesity. Diabetic retinopathy and diabetic nephropathy are two main complications of DM. Some studies suggest a correlation between diabetic nephropathy and diabetic retinopathy. However, other studies found that renal cortex echogenicity is associated with chronicity of kidney disease and renal histopathology. The aim of this study was to determine whether there is a correlation between renal cortex echogenicity as determined by renal ultrasonography and degree of retinopathy as determined by funduscopy in subjects with DM.MethodsA cross sectional study was conducted on 41 DM subjects from September to November 2014. Data obtained by anamnesis, physical examination, and examination of ureum, creatinine, urinalysis, glycated hemoglobin (HbA1c), renal and urinary tract ultrasonography and funduscopy, were collected from all subjects. Blood samples were taken from the median cubital vein for biochemical measurements using COBAS automated analyzers. Normality of data distribution was tested using the Shapiro-Wilk test. To determine the relationship between variables the Spearman correlation test was used. ResultsUsing the Spearman correlation test, a strongly significant correlation was found between degree of renal cortex echogenicity and degree of retinopathy (r=0.773; p=0.0001). A significant relationship was also found for the degree of retinopathy with age (r=0.317; p=0.044), duration of diabetes mellitus (r=0.639; p=0.0001) and HbA1c (r=0.681; p=0.001).ConclusionThis study found that renal cortex echogenicity increased the degree of diabetic retinopathy in diabetic subjects. Renal ultrasonography for patients with type 2 DM has a great role in diagnosing and grading diabetic retinopathy.